(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
It is debatable if population increase and economic growth are linked. This article uses historical statistics to show how people growth, per person production growth, and overall economic growth have all correlated during the last 200 years. Low growing populations in rising countries is expected to produce societal and economic problems, while fast demographic development in low-income countries is expected to hinder development. Several individuals are opposed to foreign immigration that might help to alleviate these inequalities. Reduced populations explosion and restricted immigration, so based income imbalance evaluations, may contribute to higher factors such as economical imbalance. The ideas of broad, goal, and sample frame are described in this article in response to errors and disputes surrounding them, as well as the fact that the links between them have never been explained in the context of a formal research. Based on a general situation, these principles are explored in this paper. In a qualitative study with a big study population, we generally try to explain why it is important to identify the general, target, and accessible audiences. In qualitative research, the study shows how the research objective, settings, and assumptions may influence the contents and intensity of the target and accessible population.